SPAK and OSR1 Dependent Down-Regulation of Murine Renal Outer Medullary K+ Channel ROMK1 - Bernat Elvira; Carlos Munoz; Jose Borras; Hong Chen; Jamshed Warsi; Sumant Singh Ajay; Ekaterina Shumilina; Florian Lang (Karger Publishers, 2014)
Background/Aims: The kinases SPAK (SPS1-related proline/alanine-rich kinase) and OSR1 (oxidative stress-responsive kinase 1) participate in the regulation of the NaCl cotransporter NCC and the Na+,K+,2Cl- cotransporter NKCC2. The kinases are regulated by WNK (with-no-K[Lys]) kinases. Mutations of genes encoding WNK kinases underly Gordon's syndrome, a monogenic disease leading to hypertension and hyperkalemia. WNK kinases further regulate the renal outer medullary K+ channel ROMK1. The present study explored, whether SPAK and/or OSR1 have similarly the potential to modify the activity of ROMK1. Methods: ROMK1 was expressed in Xenopus oocytes with or without additional expression of wild-type SPAK, constitutively active T233ESPAK, catalytically inactive D212ASPAK, wild-type OSR1, constitutively active T185EOSR1 and catalytically inactive D164AOSR1. Channel activity was determined utilizing dual electrode voltage clamp and ROMK1 protein abundance in the cell membrane utilizing chemiluminescence of ROMK1 containing an extracellular hemagglutinin epitope (ROMK1-HA). Results: ROMK1 activity and ROMK1-HA protein abundance were significantly down-regulated by wild-type SPAK and T233ESPAK, but not by D212ASPAK. Similarly, ROMK1 activity and ROMK1-HA protein abundance were significantly down-regulated by wild-type OSR1 and T185EOSR1, but not by D164AOSR1. Conclusion: ROMK1 protein abundance and activity are down-regulated by SPAK and OSR1.